Analisis Penyebab Tingginya Reject Produk pada Area Warehouse Menggunakan Metode Pareto, 5 Why Analysis, dan Fishbone Diagram - Rizal Deokosta; Muhammad Ifdol; Hilman Mubarik Aziz; Immanuel Wijaya Huwae; Yudi Prastyo (Journal of Engineering and Applied Technology, 2026)
The high rate of product rejection within the warehouse area compromises spatial efficiency and escalates logistics expenses in automotive manufacturing. This empirical study constructs a structured diagnostic interventional framework using Pareto charts, Fishbone diagrams, and 5 Why analysis to mitigate storage quality failures. Baseline evaluations revealed that the initial defect rate peaked at 5.20% (520 rejected units), significantly violating the 3.0% corporate tolerance threshold, with material damage and misplacement contributing a substantial 76.92% cumulative total. To address these layout and procedural root causes, engineering interventions were deployed, including warehouse redesign, shared storage, rigid pallet stacking limitations, standardized visual labeling, and operator competency training. Post intervention comparative analysis demonstrated an exceptional recovery in operational reliability, successfully driving the rejection rate down to 2.8% (280 units). This systematic reduction demonstrates the robust efficacy of integrating statistical quality metrics with spatial engineering to achieve sustainable operational excellence in modern industrial warehousing.